Detection of extended Red Clump in the SMC cluster Kron 3. Issue Volume 14:Issue S351(2019) (May 2019) - Nayak, P. K.; Subramaniam, A.; Subramanian, S.; Sahu, S.; Mondal, C.; Cioni, Maria-Rosa L.; Bell, C.
Abstract: For the first time, we report the identification of NUV bright red clump (RC) stars and the extension of RC stars over two magnitudes both in color and magnitude axis in NUV vs (NUV – optical) color magnitude diagram. We find that the extension of RC is not due to photometric uncertainties. We suggest that the extension could be an effect of field star contamination. We also suggest that if it is an intrinsic property of the cluster then age and/or metallicity spread within the cluster could be the possible reasons for extended RC.